2015
DOI: 10.2134/cftm2015.0175
|View full text |Cite
|
Sign up to set email alerts
|

Input‐based Stress Management Fails to Increase Soybean Yield in Kentucky

Abstract: Soybean producers have recently adopted management systems that attempt to manipulate plant stress throughout the growing season in an effort to increase yield. The purpose of this study was to determine if management systems that utilize crop inputs to manipulate soybean stress can increase soybean seed yield. Inputs designed to affect soybean stress were applied to early‐maturity (2.8 relative maturity [RM]) and full‐season (4.5 RM) soybean at three locations in Kentucky throughout the 2013 and 2014 growing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 24 publications
3
8
0
Order By: Relevance
“…Similarly, this study did not observe increased seed yield with the defoliant. These findings support recent studies which also did not observe increased seed yield with defoliant use (Gregg et al, 2015; Orlowski et al, 2016; Mangialardi et al, 2016). Finally, increased seed yield was not observed for N,N’‐diformyl.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Similarly, this study did not observe increased seed yield with the defoliant. These findings support recent studies which also did not observe increased seed yield with defoliant use (Gregg et al, 2015; Orlowski et al, 2016; Mangialardi et al, 2016). Finally, increased seed yield was not observed for N,N’‐diformyl.…”
Section: Discussionsupporting
confidence: 92%
“…Finally, increased seed yield was not observed for N,N’‐diformyl. A lack of seed yield response to N,N’‐diformyl was also reported by Gregg et al (2015).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Henry et al (2011) and Orlowski et al (2016) observed soybean yield increases of 3.5 and 4.6% from pyraclostrobin applications, respectively, in the absence of disease. In contrast, Swoboda and Pedersen (2009), Gregg et al (2015), and Ng et al (2018) found no differences in soybean grain yield from fungicide applications within an environment lacking disease pressure.…”
Section: Utilizing Multiple Inputs To Improve Soybean Productionmentioning
confidence: 76%
“…During this same time, soybean yield and total acres planted in Michigan increased by 8 and 28%, respectively (USDA‐NASS, 2017). Increased prices paid and commercial marketing have encouraged soybean producers to adopt high‐input management in which a greater number of agronomic inputs are applied to maximize yield and profitability (Gregg et al, 2015; Marburger et al, 2016; Orlowski et al, 2016). Additionally, increased adoption of intensive soybean systems combined with the introduction of new genetics have some individuals questioning older (>20 years) university nutrient recommendations (Vitosh et al, 1995; Fulford and Culman, 2018).…”
Section: Utilizing Multiple Inputs To Improve Soybean Productionmentioning
confidence: 99%